Endothelin-1 Exhibiting Pro-Nociceptive and Pro-Peristaltic Activities Is Increased in Peritoneal Carcinomatosis - Greco, Céline; Basso, Lilian; Désormeaux, Cléo; Fournel, Audren; Demuynck, Benedicte; Lafendi, Leila; Chapiro, Sylvie; Lemoine, Antoinette; Zhu, Ying-Ying; Knauf, Claude; Cenac, Nicolas; Boucheix, Claude; et al. (Frontiers in Pain Research, 2021)
Background: Peritoneal carcinomatosis often results in alterations in intestinal peristalsis and recurrent abdominal pain. Pain management in these patients is often unsatisfactory. This study aimed to investigate whether endothelin-1 (EDN1) was involved in pain mediation in peritoneal carcinomatosis, and thus whether the EDN1 pathway could be a new therapeutic target for peritoneal carcinomatosis-associated pain. Methods: EDN1 plasma levels and abdominal pain severity were assessed in patients with abdominal tumors, with or without peritoneal carcinomatosis, and in healthy donors. The effects of EDN1 on the visceromotor response to colorectal distension, and on colonic contractions were then examined in mice, and the mechanism of action of EDN1 was then investigated by measuring the impact of EDN1 exposure on calcium mobilization in cultured neurons. Inhibition studies were also performed to determine if the effects of EDN1 exposure could be reversed by EDN1-specific receptor antagonists. Results: A positive correlation between EDN1 plasma levels and abdominal pain was identified in patients with peritoneal carcinomatosis. EDN1 exposure increased visceral sensitivity and the amplitude of colonic contractions in mice and induced calcium mobilization by direct binding to its receptors on sensory neurons. The effects of EDN1 were inhibited by antagonists of the EDN1 receptors. Conclusions: This preliminary study, using data from patients with peritoneal carcinomatosis combined with data from experiments performed in mice, suggests that EDN1 plays a key role mediating pain in peritoneal carcinomatosis. Our findings suggest that antagonists of the EDN1 receptors might be beneficial in the management of pain in patients with peritoneal carcinomatosis.